Phraseological Units and Principles of M.Umarkhodzhaev (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
when discussing phraseological units, classification issues come to the fore. The article does not talk about any classification, but about the nature and function of phraseology, their independence and relationship with other linguistic units, which allows you to create a general idea of this phenomenon.